Assessment of Salivary Flow Rate in Edentulous Patient - Nurul Afiqah Amani Binti Zaaba1 , Dhanraj2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Complete denture help to re-establish the occlusion and aesthetic to such extent it mimic the previously missing teeth and other features which may be lose over the time. In a complete denture wearer, saliva is responsible for the retention of the prosthesis due to its lubricating function. It also aid in integrity, adhesion and stabilisation of dentures in position after the placement. It act as interposed salivary film which allowed the prosthesis to lie on the film rather than on the bare mucosa. This would help to protect the tissues from the hydration and forces of the denture base that acting on it. Therefore, maintaining normal pH and salivary flow rate is required, in order to achieve a better retention of denture as well as good oral health. Aim: To investigate the relationship between the salivary flow rate before and after the placement of complete denture. Materials and Method: There were 15 participants in the age group of 55 to 70 years old, which required complete denture prosthesis for the first time. The unstimulated or resting whole saliva and stimulated whole saliva was collected by using spitting method. Saliva production was stimulated by chewing paraffin wax. The time taken for saliva collection of 5 mL was recorded by using stopwatch. The data obtained was analysed by using paired t-test. Results: There was significant difference between the unstimulated whole salivary flow rate and stimulated whole salivary flow rate before the placement of the denture, which was by 0.20 mL/min. Whereas, the difference between the unstimulated whole salivary flow rate and stimulated whole salivary flow rate after the placement also show significant changes which was about 0.14 mL/min. Chewing of paraffin wax as well as placement of denture act as stimulatory agents in production of saliva. Conclusion: Stimulated salivary flow rate were higher than the unstimulated salivary flow rate which obtained before and immediately after the placement of complete denture. There was significant differences of the salivary flow rate before and after the placement of denture.